Passos para a elaboração de um curso de EAP para pós-graduandos em Ciência da Computação - Vieira, Bruna Gabriela Augusto Marçal [UNESP] (2014)
This research aimed at raising the characteristics of Computer Science graduate students related to the use of the English language in academic settings and, based on them, developing stages for an English for Academic Purposes (EAP) writing course for such an audience. The characteristics of the students were raised by means of a detailed Needs Analysis process, in which a questionnaire, interviews and a written test were applied to Computer Science students from 25,71% of public Brazilian universities. Needs Analysis raised information about present-situation, target-situation, lacks and the desires of the students, as well as the relevant content to be addressed in an EAP writing course for the target audience. Based on data from the Needs Analysis process, content was chosen, learning goals were delimitated, authentic materials were selected, relevant course units for the target audience were defined, and examples of tasks were designed (HYLAND, 2004). Needs Analysis showed that, among other things, the knowledge of the students related to the English language is adequate to academic written communication, that they have medium knowledge about academic register, and fair knowledge about the genres they have to produce in such a context. In light of the considerable differences between the characteristics of the participants of the present research and the characteristics of non-native participants of other researches in the area (SWALES, 1990, 2004; DUSZAK, 1994; JORDAN, 1997; PALTRIDGE, 2001; ROBINSON, STRONG, WHITTLE & NOBE, 2001; ARANHA, 2002; VON STAA, 2003; HYLAND, 2004 – among others), which tend to encounter difficulties when writing in English, it is possible to assume that a course for students who fit such characteristics also differs from other courses found in the literature, once it may not include tasks to develop students´ knowledge about neither the English language nor the academic register, and more time can be ...